PERAN KONSELOR KRISTEN DALAM MENANGANI PECANDU NARKOBA SECARA HOLISTIK - Saragi Napitu, Marojahan; Estherina Andhi Juniva; Wikanto (STT IKSM SANTOSA ASIH, 2025)
Drug abuse severely damages all aspects of human life, including physical, biological, psychological, and social well-being. The significant impacts on drug users include disability, economic loss, and even death. Observations indicate that the destructive impact of drug use in Indonesia reaches approximately 3 million people and should be addressed seriously. Therefore, the widespread role of Christian counselors is essential. The research used an applied research method, in which researchers solve practical problems. Applied research is a methodology based on utility. This research focuses more on solving practical problems. Solving problems based on real-life events in the social environment. In fact, biblical psychological treatment is highly recommended. Another tendency of drug influence is xenophobia, which is an excessive (irrational) fear of something foreign or foreign customs. Professional psychological treatment built on a humanitarian (humanist) basis, a strong belief in the capabilities of the human person, is not recommended. This means that our psychological theory and practice must align with biblical truth. Because humanistic psychology cannot be replaced by Christianity, but must be integrated with biblical ideas. Christian psychologists and/or Christian counselors are strongly advised to have a commitment and dependence on the power and guidance of the Holy Spirit. This should be recommended by doctors, medical personnel, and facilitators, so that treatment is holistically complete; freeing oneself from the power of sin, the bondage of drug addiction, and transforming into godly people.